Berpikir Kritis Siswa dalam Menyelesaikan Soal AKM Konten Geometri Ditinjau dari Gaya Kognitif Field Dependent dan Field Independent - Alfaini Hidayatul Lail; Susanah Susanah (Universitas Negeri Surabaya, 2026)
Critical thinking is an essential element in mathematics learning as it relates to students’ mental processes in understanding, analyzing, and solving problems logically and systematically, particularly in contextual tasks such as the minimum competency assessment (AKM). This study aimed to describe the process of students’ critical thinking based on Field Independent and Field Dependent cognitive styles in solving AKM geometry problems. This research employed a descriptive qualitative approach. The research subjects consisted of one student with a Field Dependent cognitive style and one student with a Field Independent cognitive style. Data were collected through AKM numeracy tasks on geometry content and semi-structured task-based interviews. Data were analyzed based on indicators of the critical thinking process, including interpretation, analysis, inference, evaluation, explanation, and self-regulation. The results showed that the student with a Field Independent cognitive style demonstrated a complete and consistent critical thinking process across all aspects, as evidenced when students categorize relevant information, analyze problems systematically, perform calculations according to appropriate procedures, examine evidence, draw logical conclusions, and apply self-regulation through reviewing and correcting errors. Meanwhile, the student with a Field Dependent cognitive style demonstrated only some aspects of the critical thinking, particularly inference, evaluation, and explanation, while experiencing limitations in interpretation, analysis, and self-regulation The findings imply that mathematics learning should accommodate differences in students’ cognitive styles by providing more structured guidance for Field Dependent students, particularly in interpreting information, organizing problem-solving procedures, and developing self-regulation skills when solving contextual mathematical problems.